ChemInform Abstract: Slow Spin Dynamics Between Ferromagnetic Chains in a Pure‐Inorganic Framework. Issue 6 (11th February 2014) - David, Renald; Kabbour, Houria; Colis, Silviu; Mentre, Olivier
Abstract The new compound BaCo2 (As3O6)2·2H2O is prepared from a mixture of BaCO3, CoCl2, As2O3, H2O, and N2H4 (autoclave, 493 K, 72 h) and characterized by single crystal XRD, magnetic measurements, and DFT calculations.